Comparison between audio-vestibular findings and contrast-enhanced MRI of inner ear in patients with unilateral Ménière’s disease - Leng, Yangming; Fan, Wenliang; Liu, Yingzhao; Xia, Kaijun; Zhou, Renhong; Liu, Jingjing; Wang, Hongchang; Ma, Hui; Liu, Bo (Frontiers in Neuroscience, 2023)
Objective: The diagnosis of Ménière's disease (MD), characterized by idiopathic endolymphatic hydrops (ELH), remains a clinical priority. Many ancillary methods, including the auditory and vestibular assessments, have been developed to identify ELH. The newly emerging delayed magnetic resonance imaging (MRI) of the inner ear after intratympanic gadolinium (Gd) has been used for identifying ELH in vivo. We aimed to investigate the concordance of audio-vestibular and radiological findings in patients with unilateral MD. Methods: In this retrospective study, 70 patients with unilateral definite MD underwent three-dimensional fluid-attenuated inversion recovery (3D-FLAIR) sequences following intratympanic application of Gd. Audio-vestibular evaluations were performed, including pure tone audiometry, electrocochleogram (ECochG), glycerol test, caloric test, cervical and ocular vestibular evoked myogenic potentials (VEMPs), and video head impulse test (vHIT). The relationship between imaging signs of ELH and audio-vestibular results was investigated. Results: The incidence of radiological ELH was higher than that of neurotological results, including the glycerol test, caloric test, VEMPs, and vHIT. Poor or slight agreement was observed between audio-vestibular findings and radiological ELH in cochlear and/or vestibular (kappa values < 0.4). However, the pure tone average (PTA) in the affected side significantly correlated with the extent of both cochlear (r = 0.26795, p = 0.0249) and vestibular (r = 0.2728, p = 0.0223) hydrops. Furthermore, the degree of vestibular hydrops was also positively correlated with course duration (r = 0.2592, p = 0.0303) and glycerol test results (r = 0.3944, p = 0.0061) in the affected side. Conclusions: In the diagnosis of MD, contrast-enhanced MRI of the inner ear is advantageous in detecting ELH over the conventional audio-vestibular evaluations, which estimates more than hydropic dilation of endolymphatic space.